MANAJEMEN MITIGASI BAHAYA RUANGAN TERTUTUP DI KAPAL - Wahyudi Santoso; Yulianto Yulianto (Jurnal Universal Technic, 2022)
Accidents in enclosed spaces of ships that result in physical injury or death are evidence and a challenge for the maritime industry that appropriate steps and actions are needed to break the chain of similar mistakes. The aim of this research is to know the characteristics, compartments, hazards and how to manage hazards in closed spaces. Researchers used the literature review method, by digging up sources from books, laws and regulations, journals, maritime publications and others. The results of the research, hazard mitigation in enclosed spaces begins with risk assessment, followed by the correct procedures for closed room entry (before, during and after), particular responsibilities (Captain to Rating), organized assistance measures (if a victim falls) and the implementation of the Drill. according to SOLAS 74